Testing a speculative bubble in the dry bulk shipping market: a multi-factor approach. Issue 3 (2016) - Cocconcelli, Luca; Medda, Francesca
The dry bulk industry witnessed a boom and bust phase between 2005 and 2010. The aim of this work is to assess whether this pattern was driven by speculation or was a supply and demand outcome. In order to evaluate the presence of speculation, a global multi-factor risk model is implemented to estimate the long-term (cointegration) relationship between freight rates and cargo prices. The empirical results obtained suggest that a speculative period took place in the dry bulk industry between 2005 and 2011.